Patrones de diversidad de hormigas del bosque seco de la región sur del Ecuador - Vélez Pintado, Manuel Isidoro (2015)
Field work for this study, “Ant diversity patterns in dry forests of southern Ecuador, was undertaken during october 2014 in the Zapotillo sector and Laipuna Natural Reserve of Zapotillo and Macara cantons respectively to determine richness, abundance, and functional groups in these dry forests. Richness was estimated with manual capture, and 20 pitfall traps separated 20m from each other at surface level during 24 hours. Each trap contained a water-soap solution up to ¼ its depth. Abundance was calculated using the Shannon and Simpson indices using specimens from the pitfall traps. Functional groups were obtained based upon collected specimens, using ecological criteria for the classification of each group. The results include 29 species belonging to 17 genera from 6 subfamilies. Laipuna has 25 species, of which 12 are only known from the reserve, whilst in El Chilco 17 species were recorded, of which 4 are exclusive to the site. The Shannon Index shows medium diversity for both localities and the Simpson index high dominance. Additionally 6 functional groups were identified: generalist omnivores with 12 species, arboreal with 7 species, epigeic generalist predators with 2 species, nomadic predators with 2 species, foilage fungus growers with 1 species, and detritus fungus growers with 1 species.